Deoxygenative Transformation of Carbonyl and Carboxyl Compounds Using gem-Diborylalkanes - Hu, Yue; Sun, Wei; Liu, Chao (Synlett, 2019)
gem-Diborylalkanes serve as privileged carbanion precursors for the efficient construction of carbon–carbon bond with various carbonyl and carboxyl compounds. We highlight the recent advances on deoxygenative transformation of carbonyl and carboxyl compounds using gem-diborylalkanes reagents. Our recent development of a dual functionalization of gem-diborylalkanes through deoxygenative enolization with the carboxylic acids is also discussed.1 Introduction2 Activation Modes of gem-Diborylalkanes3 Deoxygenative Transformation of Carbonyl and Carboxyl Compounds via α-Diboryl Carbanion3.1 Reaction with Aldehyde and Ketone Electrophiles3.2 Reaction with Carboxylic Acid Derivatives4 Deoxygenative Transformation of Carbonyl and Carboxyl Compounds via α-Monoboryl Carbanion5 Conclusion
Keywords: gem-diborylalkanes; carbonyl compounds; carboxylic acids; deoxygenative; carbanion; electrophiles